Hubungan Kesabaran dengan Tingkat Efikasi Diri pada Mahasiswa Fakultas Kedokteran Tahap Sarjana Universitas Malahayati - Nur Sam Heni Mutiara; Sri Maria Puji Lestari; Supriyati Supriyati; Asri Mutiara Putri (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2023)
Self-efficacy according to Bandura is an individual's belief in the ability of an individual to organize and take the necessary actions to achieve certain results. Mukti and Tentama suggest that there are two factors that influence self-efficacy, namely internal factors and external factors. One component of the internal factor is patience. To determine the relationship between patience and the level of self-efficacy in undergraduate students of the Faculty of Medicine, Malahayati University. This type of research is an observational quantitative analytic study with a cross-sectional research design, the measuring instrument used is a questionnaire on the patience scale and self-efficacy level scale and uses a stratified random sampling technique. Spearman test statistical data using the SPSS program. Based on the research results, there were 228 students with the highest level of patience in the high category, totaling 129 students (56.6%), then for the highest level of self-efficacy in the high category, amounting to 140 students (61.4%). Statistical analysis using the Spearman test showed a p = value of 0.000 with a correlation test of 0.357. There is a significant relationship between patience and the level of self-efficacy in undergraduate students of the Faculty of Medicine, Malahayati University. Patience affects the level of self-efficacy by 15.4%.